2022
DOI: 10.1186/s12893-022-01851-1
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute appendicitis during the COVID-19 pandemic: a retrospective cohort study

Abstract: Background The Coronavirus Disease 2019 (COVID-19) pandemic profoundly impacted delivery of health care. South Western Sydney Local Health District (SWSLHD) experienced some of the highest cases, admissions and deaths during the Delta and Omicron waves in New South Wales. This study aims to determine the impact of the pandemic on emergency surgery services for adults presenting with acute appendicitis. Methods A retrospective review of patient reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…An et al recognized the median duration of symptoms before admission was six hours longer during the pandemic compared to the pre-pandemic period (18 vs. 24 hours) [6]. Meanwhile, Tankel et al and Francombe et al did not find any significant difference in the duration of symptoms (1.5 vs. 1.8 days, and 2.2 vs 2.3 days, respectively) [10,19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An et al recognized the median duration of symptoms before admission was six hours longer during the pandemic compared to the pre-pandemic period (18 vs. 24 hours) [6]. Meanwhile, Tankel et al and Francombe et al did not find any significant difference in the duration of symptoms (1.5 vs. 1.8 days, and 2.2 vs 2.3 days, respectively) [10,19].…”
Section: Discussionmentioning
confidence: 98%
“…Coronavirus disease 2019 (COVID- 19) is the name of an infectious condition caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which was first identified in the beginning of 2020 in China. After being declared by the World Health Organization (WHO) as a pandemic on March, 11th 2020, the COVID-19 pandemic rapidly spread and profoundly influenced healthcare systems worldwide [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Pandemic studies have conflicting results on symptom duration before presentation, 24,25,29 but most have found a higher rate of complicated appendicitis during the pandemic. 24,32 In our study, 42% of patients presented with complicated appendicitis, which agrees with published literature of more advanced presentations during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Forssten et al 28 reported no difference in American Society for Anesthesiologist physical status class between COVID groups, with the majority being American Society for Anesthesiologist class 1 or 2. In addition, Frankcombe et al 29 reported that 12 asymptomatic COVID-positive patients underwent appendectomy for AA without adverse outcomes. Together, these results suggest that a positive COVID-19 test alone should not exclude patients from appendectomy for AA.…”
Section: Discussionmentioning
confidence: 99%
“…The standard of care for acute appendicitis is generally considered to be laparoscopic appendectomy, although with some consideration of antibiotic therapy as a potential treatment for certain indications [9][10][11][12]. There has been significant interest surrounding the effects of the COVID-19 pandemic on volume, severity, and treatment of acute appendicitis, with evidence supporting an increase in the rate of antibiotic treatment for acute appendicitis during the pandemic as well as higher rates of complicated and perforated appendicitis observed in adults [10,[13][14][15][16][17][18]. Additionally, as society continues to adapt to live with COVID as a potentially permanent part of the healthcare landscape, there has been little research into how the continued adaptions around COVID-19 affect how surgical systems function today.…”
Section: Introductionmentioning
confidence: 99%